Congenital thiopurine methyltransferase deficiency and 6-mercaptopurine toxicity during treatment for acute lymphoblastic leukaemia. Issue 5 (November 1993) - Lennard, L; Gibson, B E; Nicole, T; Lilleyman, J S
Abstract : Two children with acute lymphoblastic leukaemia (ALL) taking daily 6-mercaptopurine as part of a national UK therapeutic trial repeatedly developed profound myelosuppression on 25% of the standard protocol dose. Both were found to have undetectable intracellular activity of thiopurine methyltransferase (TPMT), an enzyme controlling one of the major alternative catabolic pathways of 6-mercaptopurine, and both produced higher concentrations of cytotoxic drug metabolites at 10-25% of the protocol dose than other patients taking 100%. It is supposed that these patients represent the 0.33% of the normal population constitutionally lacking TPMT. It is important to recognise such individuals both to avoid fatal bone marrow failure through inadvertent overdosage, and to be reassured that an adequate drug effect can be achieved at around 10% of the standard dose.